Regression analyzes to determine the selection targets in the central self-performance test in Limousin cattle breed: Short communication - Tőzsér, János; Szűcs, Márton (Animal welfare, Ethology and Housing Systems (AWETH), 2020)
The authors analysed the self performance test results of Limousin (n=40) pure bred sire candidates obtained between the years of 2018 and 2020. Sire candidates were kept in small group (2-9) in pen at the Self Performance Test Station and their feeding was based on ad libitum grass hay, or alfa-alfa hay and rationed bull’s feed. Analyzed characteristics were as follows: finish live weight (FLW), five body measurements (eg: withers’ height, pin with, width of shoulders, cm), and genomic scores (GS) for 2 traits (eg: muscularity -, size of bone score). Data were processed using SPSS 25. program package: backward regression analysis was applied. Finally, it was verified by backward regression that FLW (y) of bulls is mainly determined by the width of shoulders and the withers height (R= 0.74, P≤0.0001, std. error of the estimate: 33.9 kg). In the second study the withers height (y) was predicted finish live weight and genomic score for size of bone (R= 0.62, P≤0.0001, std. error of the estimate: 2.9 cm). These information coud be used the breeders to develope the breeding goals in the practice.
Keywords: Limousin sire candidates; central self performance test station; stepwise regression analysis backward method; body measurements; genomic scores